2017
DOI: 10.1002/slct.201700150
|View full text |Cite
|
Sign up to set email alerts
|

‘4+1’ Mixed Ligand Strategy for the Preparation of 99m Tc-Radiopharmaceuticals for Hypoxia Detecting Applications

Abstract: The ‘4+1’ mixed ligand strategy enables radiolabeling of biomolecules with 99mTc at low ligand concentration without affecting it's in vivo biological activity. The ‘4+1’ mixed‐ligand complexes consist of central Tc(III) metal atom coordinated to a tetradentate tripodal chelator 2,2′,2′′‐nitrilotriethanethiol (NS3) and a monodentate isocyanide group tethered to a biomolecule. The present work describes the use of ‘4+1’ mixed ligand strategy to design radiopharmaceuticals for the detection of tissue hypoxia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Vats et al [49] applied the same labelling strategy using isocyanide bearing 2-and 5-nitroimidazoles. Both complexes showed moderate uptake and retention in tumour (fibrosarcoma) and favourable tumour/muscle ratios with very similar absolute values for 2-and 5-nitroimidazoles.…”
Section: Labelling Strategies Of Nitroimidazoles With [ 99m Tc]tcmentioning
confidence: 99%
See 1 more Smart Citation
“…Vats et al [49] applied the same labelling strategy using isocyanide bearing 2-and 5-nitroimidazoles. Both complexes showed moderate uptake and retention in tumour (fibrosarcoma) and favourable tumour/muscle ratios with very similar absolute values for 2-and 5-nitroimidazoles.…”
Section: Labelling Strategies Of Nitroimidazoles With [ 99m Tc]tcmentioning
confidence: 99%
“…Molecular structure of isonitrile ligands used for labelling with technetium through the formation of 4+1 Tc(III) complexes[48,49].…”
mentioning
confidence: 99%
“…It has been observed that 99m Tc-2-MBI has high uptake in S180 tumor bearing mice as well as tumor/muscle and tumor/blood ratio were also found to be more challenging than other 99m Tc-labeled imidazole based radiotracers reported in the literature [ 20 , 21 ]. As per concern for the uptake of radiotracer in non-targeted tissues and organs such as lungs, liver and intestine, our proposed radiotracer seems to be much superior than others at 4 h post-injection [ 45 , 46 ]. To the best of our knowledge and outcomes obtained from biological evaluation, this radiotracer can be significantly use as a potential radiotracer for detection of tumor hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Several SPECT and PET radiotracers with nitroimidazole have been reported to date and have attracted attention [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. [ 18 F]FMISO is one of the most widely used PET radiotracers for imaging hypoxia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technetium-99m has been the most widely used SPECT isotope because it possesses ideal nuclide properties ( t 1/2 = 6 h, Eg = 140 keV) and rich coordination chemistry with various oxidation states and donor atom sets [ 25 ]. In addition, its in-house availability and reasonable cost have resulted in wide clinical use, especially in many developing countries and less-developed regions [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%